POPULATION DYNAMICS AND STOCK ASSESSMENT OF THE SPIDER PRAWN, NEMATOPALAEMON TENUIPES HENDERSON ALONG THE MAHARASHTRA COAST - DESHMUKH, VINAY D. (Journal of Indian Fisheries Association, 2015)
Nematopalaemon tenuipes is an important component of non-penaeid prawn resources of the northwest coast of India. During 1979-82 period it contributed 29.9% to the non-penaeid prawn and 5.6% to the total fish landings of Maharashtra. The von Bertalanffy growth parameter Loo, K and t were 77.38 mm, 1.31 and -0.02 year for the m.ales while for the 0 females these parameters were respectively 87.23 mm, 1.30 and -0.01 year. The natural mortality coefficient (M) was 3.54 and 3.52 and the average total mortality coefficient (Z) during the period was 9.09 and 7. 79 for the males and females respectively. With the exploitation rates of 0.61 and 0.55 for the males and females during the period, the total stock of the species was 26,270 tonnes and the standing stock was 3,418 to:nnes. The maximum sustainable yield (MSY) of the species under the prevailing fishing conditions was 15,744 tonnes which is close to the average yield of 14,726 tonnes from the dol nets. Hence further increase in effort is not suggested.